GNIFICAÇÃO DOS PRINCÍPIOS BÁSICOS DE CONVERSÕES DE ENERGIA LIGADOS ÀS TRANSFORMAÇÕES QUÍMICAS NA EDUCAÇÃO BÁSICA - Vianna, Jaqueline; Becker, Micheli; Neis, Marilia F.; Maldaner, Otavio A. (Salão do Conhecimento, 2013)
Resumo